Conflict resolution education in building social skills of elementary school students - Istianti, Tuti; Maryani, Enok; Maftuh, Bunyamin; Gunawan, Ahmad; Janah, Widia Nur; Nurkholiq, Agus (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
Solidarity with human diversity in groups can be built when there is a connection to moral aspects. Morals can unite humans socially and be able to lead a person to have attitudes and actions to act wisely in order to avoid conflict, how is the conflict resolution education model based on Sabilulungan local wisdom values in building social cooperation skills competencies for elementary school students? Based on the formulation of the main problem, the research steps are elaborated into several sub questions as follows: How is the factual picture of social studies learning in elementary schools so far? How is conflict resolution education based on local wisdom sabilulungan in building the competence of cooperative skills of elementary school students? Social skills are an important part that a person needs in social life when interacting with others. Cartledge and Milburn (1992) state that social skills are the ability of a person or community member to establish relationships with others and the ability to solve problems so that they can adapt harmoniously to the surrounding community. This research and development produces a product model of Conflict Resolution Education Based on Sabilulungan Local Wisdom (PRK-BKLS) which produces a model syntax consisting of 5 (five) stages, namely: exploration, logical reasoning, consensus building, decision making, and conflict resolution reflection.